Abdurauf Fitrat Created Homeland Praise (Based on Salih Bishakchi's analysis) (Eurasian Journal of Humanities and Social Sciences, 2022)
In this article described the interpretation of Abdurauf Fitrat’s literary inheritance by foreign scholars, especially by the Turkish literary critic Salih Bishakchi.